2015
DOI: 10.1093/mnras/stv921
|View full text |Cite
|
Sign up to set email alerts
|

Planetary systems and real planetary nebulae from planet destruction near white dwarfs

Abstract: We suggest that tidal destruction of Earth-like and icy planets near a white dwarf (WD) might lead to the formation of one or more low-mass − Earthlike and lighter − planets in tight orbits around the WD. The formation of the new WD planetary system starts with a tidal break-up of the parent planet to planetesimals near the tidal radius of about 1R ⊙ . Internal stress forces keep the planetesimal from further tidal break-up when their radius is less than about 100 km. We speculate that the planetesimals then b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 104 publications
(146 reference statements)
0
17
0
Order By: Relevance
“…Large substellar bodies. Bear & Soker [ 289 ] indicated that while the envelope of a massive planet that is being destroyed may form a gaseous disc, the rocky fragments could represent small planets that then migrate within the disc; Bear & Soker [ 290 ] made a similar suggestion. Alternatively, Guillochon et al [ 291 ] and Liu et al [ 292 ] intimated that a first-generation planet may be transformed into a second-generation planet by being tidally disrupted.…”
Section: Formation From Stellar Fallbackmentioning
confidence: 99%
See 2 more Smart Citations
“…Large substellar bodies. Bear & Soker [ 289 ] indicated that while the envelope of a massive planet that is being destroyed may form a gaseous disc, the rocky fragments could represent small planets that then migrate within the disc; Bear & Soker [ 290 ] made a similar suggestion. Alternatively, Guillochon et al [ 291 ] and Liu et al [ 292 ] intimated that a first-generation planet may be transformed into a second-generation planet by being tidally disrupted.…”
Section: Formation From Stellar Fallbackmentioning
confidence: 99%
“…A formulation which includes the internal strength of the SB is (rearranged from eqn 8 of [ 290 ]): where γ SB is the critical tensile strength of the SB that is disrupting. For a strengthless SB, which is representative of many ‘rubble pile’ Solar system asteroids, this equation reduces to r t ≈1.26 R ★ ( ρ ★ / ρ SB ) 1/3 .…”
Section: White Dwarf Disc Formation From First-generation Substellar mentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of these uncertainties, transit signatures strongly suggest that dust is emanating from the bodies, and Roche radius computations (e.g. based on equations and discussion from Murray & Dermott 1999;Cordes & Shannon 2008;Veras et al 2014b;Bear & Soker 2015) affirm that the bodies are highly likely to be currently disintegrating.…”
Section: Introductionmentioning
confidence: 99%
“…The following spherical forces are similar in form to those presented in BVG17 and Bear & Soker (2015),…”
Section: Shape Model Comparisonmentioning
confidence: 84%